SBU Trustees Elect Richard J. Melson, Ph.D., as 26th President - Office of Marketing & Communications (Southwest Baptist University, 2021)
Southwest Baptist University’s Board of Trustees unanimously elected Richard J. Melson, Ph.D., as the 26th president effective Sept. 7.